Analisis Sebelum dan Sesudah Dilakukan Proses Pembersihan Terhadap Performa AC Tipe Split Wall Kapasitas 1 1/2 PK - zayadi, ahmad; Yoga Utomo, Kis; Sugiaharto, Agus; S, Wismanto; HP, Cahyono; Madaskala, Ananda Revalby (FTK UNSURYA, 2021)
Air conditioning in the room functions to regulate humidity, heating and cooling the air in the room. The purpose of this conditioning is to provide comfort for the user. The process of cleaning the condenser and evaporator pipe fins can improve compressor performance. The research was conducted on an air conditioner with a capacity of 1 1/2 PK using refrigerant R-22. With an average mass flow rate of 82.5 kg/s before cleaning and 79.6 kg/s after cleaning, it decreased by 4.4%. This has an impact on refrigeration where the average value of the impact of refrigeration before cleaning is 145.4 kJ/kg and after cleaning is 150.6 kJ/kg. This means that after the cleaning process, the evaporator can increase the refrigeration in the air conditioning system by 3.4%. The parameters used are the consumption of electrical power, the temperature of the refrigerant entering and leaving the condenser, the temperature of the refrigerant entering and leaving the evaporator. The increase in compressor performance after the cleaning process is carried out, it can be seen from the total value of electrical energy use before cleaning is 10.9 kWh, and after cleaning it becomes 8.8 kWh. This has an effect on the consumption of electrical energy to drive the compressor to be more efficient by 19.26%. COP an average of 3.6 before cleaning and after cleaning to 4.9 means an increase in compressor work by 1.3 or by 26.5%. Compressor work has decreased by 4440.4 Watts or a decrease of 26.8%.